The Individualized Classroom Assessment Scoring System (inCLASS): Preliminary Reliability and Validity of a System for Observing Preschoolers’ Competence in Classroom Interactions - Downer, Jason T. (2009)
This paper introduces the Individualized Classroom Assessment Scoring System (inCLASS), an observation tool that targets children’s interactions in preschool classrooms with teachers, peers, and tasks. In particular, initial evidence is reported of the extent to which the inCLASS meets the following psychometric criteria: inter-rater reliability, normal distributions and adequate range, construct validity, and criterion-related validity. These initial findings suggest that the inCLASS has the potential to provide an authentic, contextualized assessment of young children’s classroom behaviors. Future directions for research with the inCLASS are discussed.